Support services for higher degree research students: a survey of three Australian universities. (2nd September 2016) - Silva, Pujitha; Woodman, Karen; Taji, Acram; Travelyan, James; Samani, Shamim; Sharda, Hema; Narayanaswamy, Ramesh; Lucey, Anthony; Sahama, Tony; Yarlagadda, Prasad KDV
ABSTRACT: A survey was conducted across three Australian universities to identify the types and format of support services available for higher degree research (HDR, or MA and Ph.D.) students. The services were classified with regards to availability, location and accessibility. A comparative tool was developed to help institutions categorise their services in terms of academic, administrative, social and settlement, language and miscellaneous (other) supports. All three universities showed similarities in the type of academic support services offered, while differing in social and settlement and language support services in terms of the location and the level of accessibility of these services. The study also examined the specific support services available for culturally and linguistically diverse (CALD) students. The three universities differed in their emphases in catering to CALD needs, with their allocation of resources reflecting these differences. The organisation of these services within the universities was further assessed to determine possible factors that may influence the effective delivery of these services, by considering HDR and CALD student specific issues. The findings and tools developed by this study may be useful to HDR supervisors and university administrators in identifying key support services to better improve outcomes for the HDR students and universities.